Identifikasi Morfologi Vegetatif dan Generatif Varietas Jambu Bol Gondang Manis dan Jambu Jamaika di Desa Gondang Manis Kecamatan Bandar Kedungmulyo Jombang - Nosma Firdaus; Miftachul Chusnah; Purbowo Purbowo (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this research to determine the morphological characteristics of vegetative and generative growth and the characteristics of guava bol gondang sweet and guava bol jamaica in Gondang Manis village, Bandar Kedungmulyo district, Jombang regency, East Java. The research was carried out from May to July 2021 by selecting 5 samples of guava bol gondang sweet and 5 samples of guava bol jamaica. The research was conducted by direct observation and compiled using descriptive methods, namely simplifying and organizing data to obtain an overall picture of the object being observed. This research was carried out by direct observation by taking the type of research that described in detail and systematically the growth of vegetative and generative morphology of guava varieties gondang sweet and guava bol jamaica. Based on observations of vegetative and generative morphology growth of guava plants, guava bol gondang sweet and guava bol jamaica include tree plant habitus, plant height range, leaf area, leaf width, leaf length, petiole shape, petiole color, color of the upper surface of the leaf, color of the lower surface. leaf, leaf base shape, leaf tip shape, leaf edge, leaf shape, stem color, stem circumference, stem shape, number of main branches, flower location, number of petals, flower type, flower color, fruit shape, fruit circumference, fruit weight ,flesh thickness, fruit length, purple fruit color, seed shape, number of seeds, seed weight and seed circumference. Keywords : Generative, guava gondang sweet, guava jamaica, vegetative